Flocculation of Arthrospira maxima for improved harvesting. (February 2020) - Caetano, N.S.; Martins, A.A.; Gorgich, M.; Gutiérrez, D.M.; Ribeiro, T.J.; Mata, T.M.
Abstract: The environmental impacts associated with the burning of fossil fuels coupled with growing concerns about security of energy supply, motivated the search for more sustainable forms of energy production, among which came microalgae for biofuels production. However, the commercial production of microalgae biofuels is still not competitive compared to fossil fuels, as it is necessary to solve some process bottlenecks, among which biomass harvesting, that is the focus of this work. Hence, this work intends to study the harvesting of microalga Arthrospira maxima through flocculation by pH variation and/or addition of CaCl2 as flocculant. Thus, it is described the effect of pH variation (in the range 6 to 12), followed by the addition of flocculant, on the harvesting efficiency. Results show that by pH increase over 10 using NaOH, or by flocculation using CaCl2 at a concentration of 0.2-2.0 g/L and at a 1:30 ratio (v/v) of CaCl2 /microalgae culture, it is possible to effectively harvest this microalga.